The New Innovation of Learning Strategy during Pandemic for State Islamic University of North Sumatera Students - Tribuanaswary, Tasya; Rahmadani, Putri; Dara Damanik, Emeliya Sukma (Tahta Media Group, 2022)
This paper focused on discussing about the responses of students in State Islamic University of North Sumatera about the implementation of a new innovation in learning activities during this pandemic. In this case, all information is explored through interviews and giving some several questions that related to the focus of this research. The questions are organized correspond to the key points that lead to research goals. The sample composed of four students who are regularly took part in learning activities during the pandemic which come from the different level at State Islamic University of North Sumatera. Each sample expressed their opinion on learning experience during this pandemic, such as about the new innovations that they found in teaching strategies which include the weaknesses and strengths. Therefore, the findings of this research are useful as the new knowledge that explores how the innovation can be relied in a part of learning activities optimally, accurately, and easily in achieving the learning goals, which can be a reference for the advancement of learning activities in Indonesia, especially in State Islamic University of North Sumatera.